Training as a Type of Grounding Experts on Forensic Air Technical Examinations - Kurdes, Oleg (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2021)
The article emphasizes the lack of an effective administrative and legal mechanism in Ukraine for conducting internships for forensic experts including internships for forensic experts in conducting forensic air technical examinations that is a significant issue of their professional training. The need to develop and approve at the level of central executive body a unified legal act on organization of professional training of forensic experts where a separate section should be devoted to the internship issue. Shortcomings in the procedure for conducting internships of forensic experts and gaps in the current legislation on this issue are highlighted. Scientific principles of improving this type of training are outlined. Emphasis is placed on the lack in the Register of methods of forensic examinations of the Ministry of Justice of Ukraine methods of forensic examinations according to the 10.25: Research on aviation events and incidents forensic expert specialization and the need for its development that should be a methodological basis for forensic expert training in this forensic expert specialization.
Стажування як вид підготовки експертів до проведення авіаційнотехнічних експертиз
Keywords: forensic science institution; forensic air technical examination; forensic expert; training; internship; trainee